A generalised methodology for analytic construction of 1:1 resonances around irregular bodies: Application to the asteroid Ryugu's ejecta dynamics. (January 2020) - Soldini, Stefania; Takanao, Saiki; Ikeda, Hitoshi; Wada, Koji; Yuichi, Tsuda; Hirata, Naru; Hirata, Naoyuki
Abstract: An analytic construction of 1:1 resonances around irregular bodies is here investigated. A SPH-Mas based gravity model allows a semi-analytic expression of the linearised equations around the equilibrium points. Depending on the sphere packing distribution, the SPH-Mas model can retrieve the same dynamical objects common to others gravity models (i.e. spherical harmonics and polyhedron) or for non uniform density objects. This model has the advantage to define the same particles mesh distribution for both astrophysical and astrodynamics tools and it is computationally optimised for Matlab. The Hayabusa2's Small Carry-on Impactor operation is used as a scenario to study the ejecta particle dynamics around an irregular body. The goNEAR tool was used to simulate the impact operation in a non-linear sense when the effect of the solar radiation pressure perturbation is taken into account for particles size of 10 cm, 5 cm, 1 cm and 1 mm in diameter.